A smartphone app for preschool wheezing and reliability of medical history collection - Nicola Ullmann; Adriana Fracchiolla; Alessandra Boni; Valentina Negro; Federica Porcaro; Antonio Di Marco; Salvatore Tripodi; Renato Cutrera (BMC, 2024)
Abstract Background The use of mobile applications helps improving self-management in adolescents with asthma. However, no evidence is available for children with preschool wheezing. In addition, we have no data on the reliability of medical history collected at visits. The first aim was to assess the feasibility of a smartphone app in the management of preschool wheezing; secondly we aimed to evaluate the reliability of anamnestic data collected during face-to-face medical interviews. Methods Children with recurrent wheezing, age between 25 and 72 months, were randomly assigned to the intervention group, provided with a smartphone app for symptoms monitoring and asthma attack treatment, or to the control group, with a written action plan. At follow-up medical history was collected and the asthma control test and a clinical questionnaire were completed. App acceptability was also explored. Respiratory symptoms, medication and utilization of healthcare resources were collected. Plus, medical information obtained from the paper questionnaires was compared with data daily recorded by the app. Results We enrolled 85 preschool children with recurrent wheezing: 43 assigned to the intervention and 42 to the control group. The average (SD) adherence to e-Diary compilation was 60 (15)%. The acceptance and usability of the intervention was favorable as 70% and 93% of participants in the intervention arm described the app as ''simple and intuitive'' at Visit1 (after 3 months from enrollement) and Visit2 (3 months later than Visit1), respectively and 95% and 98% found it useful in symptoms management. There were no significant differences between the two groups in clinical outcomes. At Visit1, the cACT median score (IQR) was 23,5 (21-25) for the control group (42 patients) and 23 (21-24) for the intervention group (43 patients). At Visit2 (41 controls and 42 in the intervention group) it was 25 (24-25) and 24 (24-25), respectively. Secondary analysis of data from the intervention group showed higher incidence of daily symptoms recorded by the app in comparison with the paper questionnaire, suggesting that collection of retrospective medical history may not be completely reliable. Conclusions The smartphone app is usable and acceptable by families of preschool wheezers. Future controlled trial are needed to prove an impact on clinical outcomes or its efficacy in a telemedicine program. Finally a daily questionnaire could provide physicians with a more reliable clinical picture as reflected better daily asthma symptoms than the written retrospective questionnaire filled at clinical visit.